MEASURING THE INFLUENCE OF THE PRESSURE CHANGES ON THE GAS FLOW OF PLASMA STATISTICALLY (مجلة ديالى للبحوث الانسانية, 2022)
We studied the influence of the change in pressure on the flow of gas plasma statistically, using chi-square distribution method. Through the theoretical calculations of this method we concluded that any change in the apply pressure causes a change in the flow of gas plasma. It was a forward change, as the diagram of (pressure-the flow of the seen gas, pressure-the expected flow of the gas) relations shows.